2021
DOI: 10.3390/catal11030297
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-Catalytic Fischer–Tropsch Synthesis at Very High Pressure

Abstract: This study explored Fischer–Tropsch synthesis (FTS) by combining a non-thermal plasma (NTP), generated by an arc discharge reactor at pressures >> 1 MPa, coupled with a mullite-coated 2 wt%-Co/5 wt%-Al2O3 catalyst. The FTS product yields and electrical energy consumption for the pure plasma (no catalyst) and plasma-catalytic FTS processes were compared under the scope of various reactor operating parameters, namely, pressure (0.5 to 10 MPa), current (250 to 450 mA) and inter-electrode gap (0.5 to 2 mm). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…Various plasma-catalytic systems are used. A catalyst may be located in a plasma zone [1][2][3][4][5][6][7], an electrode may be the catalyst [8,9], and often the catalyst is located outside the plasma zone [1,[10][11][12][13][14][15][16][17][18]. This way of placing the catalyst prevents the destruction of the catalyst by plasma and the disturbance of the discharge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various plasma-catalytic systems are used. A catalyst may be located in a plasma zone [1][2][3][4][5][6][7], an electrode may be the catalyst [8,9], and often the catalyst is located outside the plasma zone [1,[10][11][12][13][14][15][16][17][18]. This way of placing the catalyst prevents the destruction of the catalyst by plasma and the disturbance of the discharge.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of introducing the catalyst into the plasma reactor, the conversion increases, which results in a reduction of the energy cost of the process. Processes such as gas purification [1][2][3], hydrogen production [5,7], Fischer-Tropsch synthesis [6] are carried out in plasma-catalytic reactors.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of C 1 to C 3 species increases with pressure when converting syngas via non-thermal plasma-catalysis. 305,[309][310][311]…”
Section: Reviewmentioning
confidence: 99%
“…Despite the advancements over the past decades, plasma-driven catalysis is mostly used in the environment remediation field (e.g., VOCs decomposition, organic pollutant degradation) or in the chemical reactions between smallmolecules (such as methanation, methanol synthesis, steam reforming and RWGS, etc. ). Although plasma has been commonly employed as a pretreatment procedure for FTS catalyst synthesis, reports on plasma-driven FTS reactions under high pressure are limited. Characterization studies on plasma-treated Co-based FTS catalysts have revealed notable benefits from direct treatment with H 2 and CO plasma.…”
Section: Steering the Structural Evolution: The Role Of Reactive Envi...mentioning
confidence: 99%